Dedicated phantom and TLD-100 dosimetry for simultaneous determination of mean glandular dose and beam quality: Proposal for a compact mammography quality control procedure. (April 2019) - Sánchez-Nieto, B.; López-Pineda, E.; Ruiz-Trejo, C.; Muñoz, I.D.; Caprile, P.; Chorbadjian, G.; Brandan, M.E.
Highlights: A TLD-100 dosimetry protocol was optimized for use on a mammographic phantom (M3D). Tube output, HVL and MGD accurately determined with few exposures of the M3D. Use of M3D phantom resulted in significant time savings in dosimetric QC tests. A "compact" mammography QC procedure (including M3D) was proposed. Results could ease the adoption, in some facilities, of a QC culture in mammography.